2012
DOI: 10.1016/j.seizure.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between iron status and febrile seizures in children

Abstract: Low serum ferritin concentration and low iron status may be risk factors for the development of febrile seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 20 publications
4
32
0
1
Order By: Relevance
“…Of the previously reported associations we examined (5-7, 9, 13-24, 26), only positive family history for FS (5) and iron deficiency (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) were risk factors in our prospective case control study.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Of the previously reported associations we examined (5-7, 9, 13-24, 26), only positive family history for FS (5) and iron deficiency (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) were risk factors in our prospective case control study.…”
Section: Discussionmentioning
confidence: 76%
“…Iron plays a critical role in the metabolism of several neurotransmitters as well as in myelination (10)(11)(12) and deficiency is associated with a number of neurological conditions in children including developmental delay, stroke, breath-holding attacks and cranial nerve palsies (11,12). Iron deficiency (ID) might therefore lower the seizure threshold (14) but there is controversy over whether there is an association with FS (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), most conducted in the Developing World (24). In this study we investigate whether there is any association between ID and occurrence of FS in Greek preschoolers.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed iron deficiency and iron deficiency anemia were more frequent in children with FS [13][14][15]; and in other research, serum and cerebrospinal fluid zinc levels of children with FS were significantly lower than in children with febrile illness and afebrile seizure [5][6][7][8][9]16].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of low serum iron was reported to be as high as 56.2% in Shiraz (Iran) and it was 30.5% in Kenya [7,10]. Also, it has been hypothesized that iron deficiency could be important in brain development and that so, it should be noticed and treated more urgently [11].…”
Section: Discussionmentioning
confidence: 99%